1991
DOI: 10.1111/j.1751-0813.1991.tb03104.x
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencephalitis and other conditions associated with Histophilus ovis infection in sheep

Abstract: Histophilus ovis was isolated from 29 sheep in 20 flocks and 2 artificial insemination (AI) centres in southern New South Wales from 1984 to 1990. The clinical and pathological findings were consistent with previous reports and included polyarthritis (7 flocks), epididymo-orchitis (5), meningoencephalitis (3), pneumonia (3), septicaemia (2), mastitis (1) and metritis (1). Six sheep had meningoencephalitis, a syndrome not previously associated with H ovis infection in sheep, which was similar pathologically to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Other presentations are abortion, generalized pyemia, metritis, mastitis, and TME. Histophilosis tends to affect lambs, with polyarthritis in younger (1-4 weeks) and septicemia in older animals (4-7 months) (Philbey et al 1991). Disease can occur as outbreaks.…”
Section: Small Domestic Ruminantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other presentations are abortion, generalized pyemia, metritis, mastitis, and TME. Histophilosis tends to affect lambs, with polyarthritis in younger (1-4 weeks) and septicemia in older animals (4-7 months) (Philbey et al 1991). Disease can occur as outbreaks.…”
Section: Small Domestic Ruminantsmentioning
confidence: 99%
“…Neurological disease occurs in some episodes, affecting both lambs and adults. As in cattle, CNS disease may occur as TME, or as suppurative leptomeningitis-ventriculitis-choroiditis (Philbey et al 1991). The means of transmission is unknown.…”
Section: Small Domestic Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…H. somni is a fastidious and slow-growing organism with low biochemical activity. H. somni is associated with a variety of conditions such as septicaemia, myocarditis, arthritis, pyaemia, mastitis, metritis, abortion, neonatal mortality, decreased fertility in ewes and rams, epididymo-orchitis, pneumo nia and thrombotic meningoencephalitis (Robert, 1956;Rahaley and White, 1977;Rahaley, 1978a;Webb, 1983b;Harris and Janzen, 1989;Philbey et al 1991;Cassidy et al, 1997). H. somni has aIso been iso lated from the vagina and vaginal fluids of c1inicaUy normal ewes (Rahaley, 1978b;Higgins et al, 1981;Harris and Janzen, 1989) and it has been suggested that the genital (Webb, 1983b) and respiratory (Philbey et al, 1991) tracts are the natural habitats of H. somni.…”
Section: Histophilus Somnimentioning
confidence: 99%
“…Other signs of the septicemic form are myocarditis (Haines et al 2004), otitis (Duarte and Hamdan 2004), mastitis (Armstrong et al 1986), conjunctivitis, and polyarthritis. In ovines, its participation has been reported in orchitis, epididimitis, mastitis (Palomares et al 2005), abortion (McDowell et al 1994, synovitis, meningoencephalitis (Philbey et al 1991;Cassidy et al 1997), septicemia, and pneumonia (Kearney and Orr 1993).…”
Section: Introductionmentioning
confidence: 96%